Health Risk Assessment of PM10 Exposure among School Children and the Proposed API Level for Closing the School during Haze in Malaysia - Norlen Mohamed; Lokman Hakim Sulaiman; Thahirahtul Asma Zakaria; Anis Salwa Kamarudin; Daud Abdul Rahim (Universiti Kebangsaan Malaysia, 2016)
Introduction: During haze, at what level should Air Pollutant Index (API) showed, public or private school be closed is not without controversy and is very much debated. Therefore, the aim of this paper is to objectively quantify the potential inhaled dose of PM10 associated with exposure at school and home microenvironments during haze. The result of the health risk assessment will be used to propose the API level for closing the school during haze episode. Methods: A hypothetical haze exposure scenario was created using the breakpoints of PM10 concentration for calculation of API and respective inhaled dose during haze. To determine the potential inhaled dose, we have considered many factors that include time spent for specific physical intensity at school and home microenvironments, age-specific and physical intensity-specific inhalation rate (m3/min), and the indoor/outdoor ratio of PM10. To calculate risk quotient (RQ), the inhaled dose was compared with the health reference dose computed based on the concentration of PM10 in the Malaysian Ambient Air Quality Standard. Results: When considering the specific exposure at each microenvironment (school and home), the potential inhaled dose of PM10 was substantially lower when school is closed for both primary and secondary school. The calculated risk quotient (RQ) indicates that primary school children are likely to be affected at slightly lower PM10 concentration (equivalent to API of 197) as compared to secondary school children. Short duration of high physical activity intensity during school breaks has contributed to a large proportion of inhaled dose among school children indicating the important to avoid physical activities during haze. Conclusion: Based on the assessment, taking into account the uncertainty of risk assessment methodology, we proposed school to be closed when API reach 190 for both primary and secondary schools. These findings and recommendations are only valid for naturally ventilated school and applicable in the context of the current API calculation system and the existing Recommended Air Quality Guideline values in Malaysia.